2010
DOI: 10.1029/2009ja015009
|View full text |Cite
|
Sign up to set email alerts
|

Reimei observation of highly structured auroras caused by nonaccelerated electrons

Abstract: [1] We present observations of highly structured, thin auroras cased by precipitation of nonaccelerated electrons on the basis of optical and particle measurements performed by the Reimei satellite near the equatorward edge of the main auroral oval. The aurora has the following characteristics: (1) A full width at half maximum (FWHM) value is as low as only ∼1.8 km from optical measurements, and ∼0.6 km from particle measurements at the ionospheric altitude, which is much smaller than previously determined. (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…This suggests that electrons were not accelerated but instead scattered due to pitch angle diffusion. Thus enhanced precipitation of the more energetic electrons of 2-6 keV energy is responsible for the diffuse aurora, in accordance with some previous studies (Ebihara et al, 2010;.…”
Section: Observationssupporting
confidence: 79%
See 2 more Smart Citations
“…This suggests that electrons were not accelerated but instead scattered due to pitch angle diffusion. Thus enhanced precipitation of the more energetic electrons of 2-6 keV energy is responsible for the diffuse aurora, in accordance with some previous studies (Ebihara et al, 2010;.…”
Section: Observationssupporting
confidence: 79%
“…Ebihara et al (2010) suggested that the diffuse aurora they observed was the visual manifestation of highly structured cold plasma in the magnetosphere. The existing structures could affect the wave-particle interaction causing precipitation of newly injected more energetic electrons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one of the causes for the morphology was suggested to be the modification of the electric field in the ionosphere [ Hosokawa et al , 2010]. In addition to the ionospheric feedback, highly structured diffuse auroras in the non‐patch shape were suggested to be a result of interchange instability in the magnetosphere [ Ebihara et al , 2010]. A Rayleigh‐Taylor type instability was also assumed to be the cause of finger‐like patches [ Shiokawa et al , 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Precipitating and trapped electrons obtained from particle measurements showed two different peak energies and anisotropy between downward and trapped ones with higher energy, which suggested that the auroral stripes and background generated by the upper band chorus and ECH, respectively. Narrow field of view imagers on the REIMEI satellite captured “smokelike auroras” images with a width of 0.6 km (FWHM) estimated by using simultaneous particle measurements [ Ebihara et al , 2010]. This spatial feature probably resulted from the interchange instability maintained mainly by pressures of high‐energy electrons and pitch angle scattering by whistler mode waves generated in the dense plasma region.…”
Section: Introductionmentioning
confidence: 99%